Synthesis and characterization of ZnxMn(1–x)Fe2O4 - Nguyen Le, My Linh; Do, Mai Nguyen (Hue University Journal of Science: Natural Science, 2025)
ZnxMn(1–x)Fe2O4 nanoparticles were successfully prepared in the isopropanol solvent with the hydrothermal method and the hydrothermal method combined with impregnation. The characterization of the samples by using X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR), and surface area analysis (BET) was conducted. The samples synthesized with the hydrothermal method had a phase composition of franklinite (Zn,Mn,Fe)(Fe,Mn)2O4. Meanwhile, the samples synthesized with the hydrothermal method combined with impregnation had the main phase composition of ZnxMn(1–x)Fe2O4. The Zn0.8Mn0.2Fe2O4 (ZnFe2O4/MnSO4 molar ratio = 4:1) sample exhibited the highest degree of structural order, with a BET surface area of 25.7 m2/g.